Experience of GIS modeling of extreme floods on Siberian rivers - Khromykh, Vadim V.; Khromykh, O.; Nakayama, D. (2021)
Results of GIS-mapping of flood zones during the spring flood season due to snowmelt for settlements located on the Tom River and the Ob River within Tomsk region (Western Siberia, Russia) are presented. “Flood” application of the Tomsk region Geoportal is created, where there are more than 40 3D models of settlements, including houses, infrastructure and current water level, which is calculated daily based on data from the nearest gauging stations. Analysis showed that the flood zone for the maximum water level covers more than 50% of the area in 19 settlements. The inundation flow simulation and evaluation of the evacuation route availability for the village of Black River showed that already after 6 hours after the start of flooding, residents of more than a third of the houses will not be able to independently reach the evacuation points. The results of this research can be used for decision-making in case of flood emergency during the flood season.